2018
DOI: 10.1136/thoraxjnl-2018-211767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of childhood pneumococcal conjugate vaccination on invasive disease in older adults of 10 European countries: implications for adult vaccination

Abstract: BackgroundPneumococcal conjugate vaccines (PCVs) have the potential to prevent pneumococcal disease through direct and indirect protection. This multicentre European study estimated the indirect effects of 5-year childhood PCV10 and/or PCV13 programmes on invasive pneumococcal disease (IPD) in older adults across 13 sites in 10 European countries, to support decision-making on pneumococcal vaccination policies.MethodsFor each site we calculated IPD incidence rate ratios (IRR) in people aged ≥65 years by seroty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 39 publications
6
93
2
4
Order By: Relevance
“…Neither was there a reduction in pneumonia among the elderly in Australia, and studies from the UK and Denmark have observed similar increases of AC-CAP in the elderly as in our study [13,14,16,27,28]. Our results are in accordance with the moderate impact of the PCV-CIP on the IPD incidence in the elderly observed both in Sweden, and in a multinational European study [8,29]. The European study reported an overall non-significant decline of 9% (CI À4% to 19%) in the IPD incidence in 2015 compared with 2009 (pre-PCV10/13 period) among subjects ≥ 65 years of age, and the incidence of non-PCV13 serotypes increased by 63% (CI 39% to 91%).…”
Section: (A)supporting
confidence: 91%
“…Neither was there a reduction in pneumonia among the elderly in Australia, and studies from the UK and Denmark have observed similar increases of AC-CAP in the elderly as in our study [13,14,16,27,28]. Our results are in accordance with the moderate impact of the PCV-CIP on the IPD incidence in the elderly observed both in Sweden, and in a multinational European study [8,29]. The European study reported an overall non-significant decline of 9% (CI À4% to 19%) in the IPD incidence in 2015 compared with 2009 (pre-PCV10/13 period) among subjects ≥ 65 years of age, and the incidence of non-PCV13 serotypes increased by 63% (CI 39% to 91%).…”
Section: (A)supporting
confidence: 91%
“…Other countries have reported IPD reduction rates ranging from 16% (Regev-Yochay et al, 2017) to 42% (Cabaj et al, 2016;Chalmers et al, 2016), and a greater decrease (65%) in PCV13 serotypes (Regev-Yochay et al, 2017) than those found in the present study. A multicentre European study reported a lower decline in IPD incidence (9%) than in the present study, with large reductions in PCV13 serotypes and an increase in non-PCV13 serotypes (63%) in 2011-2015 compared with 2009 (Hanquet et al, 2018).…”
Section: Discussioncontrasting
confidence: 75%
“…It could be necessary to improve vaccinationwith PPV23 in older people, mainly those with risk factors for IPD. PPV23 effectiveness against IPD remains unclear (Hanquet et al, 2018;Marrie et al, 2011;Jansen et al, 2009), but it is recommended in persons at risk of IPD and older people (Generalitat de Catalunya, Departament de Salut, 2018). Studies on the effectiveness of PPV23 focusing on specific serotypes and the time of vaccination should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…This could also lead to a lower estimated VE of the conjugate vaccine in Spain compared to CAPITA results from the Netherlands with a very low background PPV23 vaccination rate in the elderly population. Finally, this region of Spain has had a large reduction in circulating PCV13 serotypes due to the indirect effect of the PCV childhood immunization [29]. In a population with a significant reduction in PCV13 serotypes, the preventative potential of PCV13 is lower than in a population with a high proportion of circulating PCV13 serotypes.…”
Section: Evidence Base For Pcv13mentioning
confidence: 99%